PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR - Ruslan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low learning outcomes of science, for that done research by applying direct learning model. This research is a class action research, with the subject of this research is the students of grade VI SDN 005 Lubuk Gaung with the number of students 30 people. Based on the research results obtained data that students' learning outcomes have increased, learning outcomes obtained from the UH before the action with an average value of 63.62 increased in UH I cycle I with an average value to 78.62. At UH II increased by an average value of 84.08. The individual completeness of the basic score that was originally 13 people increased in the first cycle as many as 20 people and on the second cycle increased again to 26 people. Implementation of direct learning model can improve the performance of teachers, so as to improve the learning outcomes of science students of grade VI SDN 005 Lubuk Gaung.